NILAI MORAL DALAM NOVEL KARRUQ RI BANTILANG PINISI KARYA MUHANNIS - Aswati Asri; Andi Fatimah Yunus; Riska Riska (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Moral Values in the Novel Karruq ri Bantilang Pinisi by Muhannis. This study describes the moral value of Muhannis' KRBP novel through pragmatic theory. This type of qualitative descriptive research. The research data includes all sentences and quotes that contain moral values in the KRBP novel by Muhannis. The data source for this research is the 427-page novel KRBP by Muhannis, published by Ombak. Data collection techniques include reading, observing, and taking notes. The results of the study reveal that the moral values in the KRBP novel by Muhannis consist of: (1) the human relationship with oneself contains shame, hurt, hard work, self-awareness, sincerity, humility, and patience; (2) the human relationship with God contains prayer and praying to God; and (3) human relations with other human beings contain parental advice to children, advice to others, parental affection for children, cooperation, courtesy, and concern for others.